Rapid assessment of climate change issues in Indonesia strategic environmental assessment (SEA)-KLHS. Issue 1 (January 2021) - Umam, A H
Abstract: Strategic Environmental Assessment (SEA) or KLHS is becoming increasingly popular in Indonesia following the promulgation of government regulation No. 46 of 2016, concerning the procedures of its organization. The SEA, which was at first voluntary, is now mandatory before the integration into a regional spatial and a medium-term development plan. Therefore, this study aims to evaluate the extent to which climate change issues are addressed in the Strategic Environmental Assessment. Furthermore, several SEA documents that are very limited in Indonesia and only obtain on the internet were evaluated. The document consists of the Medium-Term Development Plan, Spatial Planning, and SEA in the mineral and energy sector. In addition, the study adopted a set of evaluation criteria used by Nadruz and Gallardo (2015) [1], which is a modification of the framework developed by Wende et al. (2012) [2]. The results showed that climate change issues in the SEA are still very diverse and not evenly distributed from various existing documents. Some SEA of the province medium-term development plan makes the issue very important while other documents do not. The SEA document of the mining sector contains 18 climate change criteria. Conversely, the spatial planning document contains 12-22 criteria, and the SEA for medium-term development plan contains 12-22 as well. From this study, it can be concluded that the issue of climate change still varies greatly in Indonesian SEA, and it is therefore not significant.